Implementation of Community Empowerment Programs in Students’ Character Education: A Systematic Literature Review - Akhiruddin Akhiruddin; Baso Witman Adiaksa; Najamuddin Najamuddin; Ashari Ashari (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
This study aims to analyze the implementation of community empowerment programs in students’ character education through a Systematic Literature Review (SLR) approach. The study employed the SLR method using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to identify, evaluate, and synthesize various research findings related to community-based character education. The research data were obtained from 25 national and international journal articles published between 2021 and 2026, sourced from Google Scholar, Scopus, DOAJ, ERIC, and accredited national journals. Data analysis was conducted descriptively and qualitatively through stages of identification, screening, eligibility assessment, and synthesis of research findings. The results indicate that the implementation of community empowerment programs in character education is carried out through various activities, such as outdoor learning, community service, social literacy programs, local culture-based education, environmental activities, and student leadership training. Community-based programs are proven to enhance students’ social responsibility, empathy, discipline, cooperation, communication skills, creativity, and leadership abilities. Furthermore, the integration of local cultural values into community programs strengthens students’ cultural identity, tolerance, nationalism, and social solidarity. The active involvement of communities, families, social organizations, and local governments also creates a more participatory and contextual educational environment. However, the implementation of community empowerment programs still faces several challenges, including low community participation, limited school resources, inadequate teacher competence, weak inter-institutional coordination, and the influence of digital technological development on students’ social interactions. Therefore, strategies for program development are needed through strengthening partnerships between schools and communities, integrating local culture into the curriculum, improving teacher competencies, enhancing government policy support, and developing technology-based community programs. This study concludes that community empowerment programs play a strategic role in building participatory, contextual, and sustainable character education in the modern era.